2021
DOI: 10.3389/fnut.2021.626254
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota and Tuberculosis: A Potential Role of Probiotics, and Postbiotics

Abstract: Tuberculosis (TB), caused by Mycobacterium tuberculosis attacking the lungs and other organs, is one of the most common infectious disease worldwide. According to the WHO's 2020 report, a quarter of the world's population were infected with M. tuberculosis, and ~1.4 million people died of TB. Therefore, TB is a significant public health concern, which requires cost-effective strategies for prevention and treatment. The microbiota has been considered as a “forgotten organ” and a complex dynamic ecosystem, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 74 publications
0
26
0
Order By: Relevance
“…However, research on them has been recently increasing. A growing number of studies have suggested that the microbiota plays an essential role in maintaining normal health, developing the immune system, and providing protection against pathogens (Khan et al, 2016;Dumas et al, 2018;Gupta et al, 2018;Liu et al, 2021). However, the impact of microbiota on host defense against M. tuberculosis infection is poorly understood.…”
Section: Microbiotamentioning
confidence: 99%
“…However, research on them has been recently increasing. A growing number of studies have suggested that the microbiota plays an essential role in maintaining normal health, developing the immune system, and providing protection against pathogens (Khan et al, 2016;Dumas et al, 2018;Gupta et al, 2018;Liu et al, 2021). However, the impact of microbiota on host defense against M. tuberculosis infection is poorly understood.…”
Section: Microbiotamentioning
confidence: 99%
“…To manage drug-resistant tuberculosis, a variety of potential strategies are being proposed, including the use of a pathogen-centric approach of developing new compounds with different mechanisms of action, repurposing drugs, using new analogues of existing anti-tuberculosis drugs, and using host-centric approaches of immunomodulators, therapeutic vaccines, immunity, and cell therapy [ 32 ]. As a form of alternative treatment, probiotics have recently been highlighted for their potential roles in controlling tuberculosis [ 33 ]. In this study, probiotics were applied to develop an alternative approach to solve the problem of antibiotic-resistant M. tuberculosis , and we have reported the anti-tuberculosis effect of P. acidilactici PMC202 isolated from Korean traditional fermented food.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of postbiotics in terms of improving health or preventing disease in humans and animals are shown in Table 1 . Moreover, in recent years, postbiotics have been considered a novel approach for cancer treatment as adjuvant therapy and in the treatment of gut-related diseases and infections, such as tuberculosis [ 11 , 12 , 13 , 14 ].…”
Section: The Health Benefit Of Postbiotics and Their Applications In ...mentioning
confidence: 99%